Mitral valve prolapse, aortic compliance, and skin collagen in joint hypermobility syndrome. - Handler, C E (1985)
Mitral valve prolapse was sought clinically and with phonocardiography and M mode and sector echocardiography in 15 women aged 22-57 years with joint hypermobility syndrome. The type III:III + I collagen ratio was measured in skin biopsy specimens and was found to be raised in seven of 10 patients sampled. Thirteen patients had increased aortic wall compliance measured by the continuous wave Doppler ultrasound technique. Ten (67%) patients had mitral valve prolapse shown by auscultatory signs or echocardiography or both--a prevalence at least three times greater than that in the general adult population. It is concluded that if the abnormality of collagen biosynthesis found in skin biopsy samples in these patients is also present in their mitral valve tissue this may predispose them to prolapse of the valve.